2013
DOI: 10.1111/j.1540-5850.2013.12001.x
|View full text |Cite
|
Sign up to set email alerts
|

A Socioeconomic Analysis of Property Assessment Uniformity: Empirical Evidence on the Role of Policy

Abstract: Though property assessment uniformity has been repeatedly studied as a technical problem related to the difficulty of the task, popular, and policy sentiment against the property tax is frequently directed at the incidence of nonuniformity across socioeconomic groups. Using data from Virginia, this paper brings socioeconomic determinants to the forefront of the analysis and their interaction with policy. Unlike the previous literature that employs controls for the time passed since the last reassessment, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…Despite studying the same state as Propheter (), the null effect is unique, a result possibly attributable to differences in estimation strategy, time period studied, and independent variables. Moreover, consistent with Ross (), counties with higher concentrations of senior homeowners assess less uniformly than counties with lower concentrations of senior homeowners. It has been suggested that the effect could be politically motivated (Ross ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Despite studying the same state as Propheter (), the null effect is unique, a result possibly attributable to differences in estimation strategy, time period studied, and independent variables. Moreover, consistent with Ross (), counties with higher concentrations of senior homeowners assess less uniformly than counties with lower concentrations of senior homeowners. It has been suggested that the effect could be politically motivated (Ross ).…”
Section: Resultssupporting
confidence: 80%
“…However, as senior concentration grows, there is less opportunity to shift tax burdens to nonseniors. Ross () found that jurisdictions in Virginia with higher concentrations of seniors had poorer assessment uniformity in nonrevaluation years than jurisdictions with lower concentrations of seniors. Thus, I expect the coefficient to be positive here.…”
Section: Model and Variable Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the complex nature of property revaluation, a body of previous literature has empirically explored the determinants of property tax assessment uniformity. The findings revealed that reducing assessment errors (revaluation lag) and improving assessment uniformity (quality) may rely on, for example, the local economy, housing market conditions, and assessor characteristics (i.e., full-time vs. part-time or local vs. state or private assessors) (Bowman & Mikesell, 1978, 1989; Ross, 2013), the number of years of experience an assessor has (Propheter, 2016), the institutional types of assessors (elected vs. appointed assessors) (Bowman & Mikesell, 1989; Lowery, 1984; Ross, 2012), the quality and quantity of the personnel (sufficient staffing with well-trained, professional assessors) (Eom, 2008; Mehta & Giertz, 1996), or neighborhood characteristics (socioeconomic status) (Allen & Dare, 2002; Heavey, 1983). In addition, in a broader manner, maintaining fair and accurate property tax assessments can depend largely on a state’s institutional constraints on local governments, including the requirements for a specific reassessment cycle 7 (e.g., annual, longer, or none) and the level of governments whose assessment functions.…”
Section: Background Of Property Tax Assessment Policy and The Case Ofmentioning
confidence: 99%
“… 2. The higher the assessment quality ratio—the more homogenous and accurate are the assessments (Bowman and Mikesell 1978; Sjoquist and Walker 1999; IAAO 2010; Ross 2013; Krupa 2015a; Propheter 2016). The lag in the coefficient of dispersion aims to correct for the endogeneity between assessment cost and assessment quality. …”
mentioning
confidence: 99%